Investigating racial disparities in drug prescriptions for patients with endometriosis - Aparajita Kashyap; Maryam Aziz; Tony Y Sun; Sharon Lipsky Gorman; Jessica Opoku-Anane; Noémie Elhadad (npj Women's Health)
Abstract We assess racial disparities in medication prescription patterns for endometriosis patients across Medicaid administrative claims data. We use ATC 3rd level drug codes to identify drug classes prescribed significantly more frequently for endometriosis patients than a comparison cohort of non-endometriosis patients. Temporal prevalence differences of prescriptions (pre- vs. post-diagnosis) were also examined. The endometriosis cohort comprised 16,372 endometriosis patients (23.3% Black, 66.0% White). Of the 28 drug classes examined, 17 were prescribed significantly less in Black patients and 4 were prescribed significantly more in Black patients. Of the 17 drugs prescribed more often in White patients, 13 have larger disparities pre-diagnosis than post-diagnosis. In the non-endometriosis cohort (n = 3,663,904), 21 drug classes were prescribed significantly more in White patients and 6 were prescribed significantly more in Black patients. Our analysis identifies disparities in prescriptions practices between White and Black endometriosis patients, notably in pain management and comorbidity treatment.